Investment Function of Economic Growth in Russia - O. S. Sukharev (Финансы: теория и практика, 2021)
The intensification of investment dynamics is a determining factor in the new growth model of the Russian economy. The Covid crisis has greatly limited the opportunities to use this factor and made restoring growth dynamics an urgent task. The aim of the study is to determine the investment function of the Russian economy before the Covid crisis in order to identify the main instruments of the investment policy of growth in the post-crisis period. The research methods are macroeconomic and regression analysis based on software Gretl 2020b, which helped to choose the investment function according to the instrument-factors. Solving the problem of collinearity of multiple regression factors makes it possible to select the best models for GDP and investment in fixed assets of the Russian economy. The research result is selected multivariate models of gross product and investment that allow considering the impact of the following instruments on the goal’s function: monetization level, key interest rate, exchange rate, risk, profitability, oil prices, financial investments, inflation. The author concludes that an increase in the monetization of the economy, a decrease in the key interest rate, and a controlled devaluation generally had a positive effect on the amount of investment in fixed assets. The investment growth increased the risk of economic activity; the decrease in profitability relatively decreased investment and increased Russia’s GDP with an increased risk over the considered time interval. When implementing investment policy, one should consider these features along with the specified macro-aggregates, the structure of investment distribution between sectors and types of investments, for example, in financial and non-financial assets. The paper shows the significance of this condition, which affects the effectiveness of the investment policy, when the shift in investment towards financial assets accompanies the slowdown in economic growth. The prospect of further research is an assessment of the equalization of sectoral risks affecting the distribution of investments and investment dynamics.